# Solve for x: [(x + 2)/(x - 3)] [(x - 2)/(x - 3)] = 1

The solution of the given equation is obtained by solving a linear equation in one variable.

## Answer: The solution to the given question [(x + 2)/(x - 3)] [(x - 2)/(x - 3)] = 1 is x = 13/6.

Let's solve the given equation.

**Explanation:**

[(x + 2)/(x - 3)] [(x - 2)/(x - 3)] = 1

[(x + 2)(x - 2)] / [ (x - 3)^{2} ] = 1

(x + 2)(x - 2) = (x - 3)^{2}

x^{2} - 2^{2} = (x - 3)^{2}

x^{2} - 4 = x^{2} - 6x + 9

-4 = - 6x + 9

6x = 4 + 9

6x = 13

x = 13/6